Peningkatan Literasi Sertifikasi Halal Skema Self Declare bagi Usaha Mikro Kecil (UMK) di Kabupaten Aceh Tengah - Ramdansyah Fitrah (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
This community service is carried out to increase halal certification literacy through a self-declare scheme for Micro and Small Enterprises (UMK) in Aceh Tegah Regency. The service team for this activity consisted of one lecturer and three students from the IAIN Takengon Sharia Banking Study Program. Activities will be carried out in May 2024 in Central Aceh Regency. Activities are carried out by providing material presentations on halal certification regulations for MSEs through the self-declare mechanism and the process of registering for halal certification with the self-declare scheme, the criteria for business actors who can participate in self-declare, the documents required for self-declare registration, and the types of products that can be self-declared. Declare. Then, I continued with Role Playing learning to increase the understanding of Food and Beverage Product MSEs regarding halal certification through a self-declare scheme. The activity results show an increase in MSEs' literacy regarding halal certification with the self-declare scheme, which then increases the interest of MSEs in registering their food and beverage products to obtain halal certificates through the self-declare scheme.